Properties of novel 0–3 PZT/silicone resin flexible piezoelectric composites for ultrasonic guided wave sensor applications - Jiang, Shuai; Shen, Yiping; Wang, Songlai; Zhi, Yulin; Han, Bin (Frontiers in Materials, 2022)
Ultrasonic guided wave (UGW) technology based on piezoelectric sensors is considered as a very promising technology for aircraft structural damage detection. Traditional piezoelectric sensors are made of Lead Zirconate Titanate (PZT) ceramics, but their brittleness and hardness make them difficult to apply to curved structure surfaces. In this paper, a novel 0-3 flexible piezoelectric composite was fabricated by dispersing PZT particles in silicone resin, and its performance for potential applications in UGW sensors was studied. The effects of polarization conditions, PZT volume fraction and PZT powder size on the performance of the composite were investigated. The influence of ambient temperature on composite performance was discussed, and temperature adaptability experiments were conducted. The results show that the optimal poling process of 0-3 PZT/silicone resin piezoelectric composite has a poling time of 25 minutes, a poling electric field of 4kV/mm, and a poling temperature of 100℃. When the sensor is required to meet the test strain range of 8,000 με, the composite should be fabricated with a PZT volume fraction of 50% and a powder size of 170~212μm to obtain optimal sensing sensitivity. At an ambient temperature range of -55℃ to 75℃, the fabricated piezoelectric composite sensor has good flexibility and sensitivity in detecting the guide wave signals. These research results provide a new flexible piezoelectric sensing technology for aircraft structural damage detection.